Acceptability and Feasibility of a Disease-specific Patient Portal in Adolescents With Sickle Cell Disease. Issue 7 (October 2019) - Kidwell, Katherine M.; Peugh, James; Westcott, Emilie; Nwankwo, Cara; Britto, Maria T.; Quinn, Charles T.; Crosby, Lori E.
Abstract : Objective: To examine the acceptability, feasibility, and efficacy of a health care portal. Observations: Adolescents and young adults with sickle cell disease were taught how to use sickle cell disease conditions page in MyChart and completed questionnaires at baseline, postintervention (T2, 6 wk after baseline) and after 3 months (T3). In total, 44 participants ( M age=18.82, SD=2.72) viewed an average of 58.07 pages from T1 to T2. The portal was highly accepted (90.32%). Efficacy data indicated that portal use was associated with improved patient-provider communication. Conclusions: Electronic portals are promising tools for improving medical self-management.